1984
DOI: 10.1084/jem.159.1.193
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous internalization of Class I major histocompatibility complex molecules in T lymphoid cells.

Abstract: A vast portion of the immunological literature has been dedicated, in the last 15 years, to the role of the major histocompatibility complex (MHC) ~ in the immune response. There is now agreement (1, 2) that the molecules coded by the genes of the MHC are essential for cellular interactions and ultimately for self, not-self distinction, at least for what concerns the response of the T system and for the production of antibodies to T-dependent antigens.In spite of the extensive efforts and of the considerable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(57 citation statements)
references
References 30 publications
2
55
0
Order By: Relevance
“…Thus, in these compartments, the peptides would dissociate from denatured MHC molecules and could undergo any necessary proteolytic processing to generate the minimal CTL epitopes. Because MHC-I molecules on T cells are known to frequently recycle through endocytic compartment (59), where, in many cases, the free exchange of binding peptides takes place (60), it is conceivable that CTL epitopes originally bound to the APC's MHC could associate with the Th cells' recycling MHC-I molecules, while en route back to the cell surface. Preliminary results showing that chloroquine treatment of Th cells inhibits the formation of CTL epitopes from Th-CTL-linked peptides presented by pAPC provide support to this possibility (A. Undale, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in these compartments, the peptides would dissociate from denatured MHC molecules and could undergo any necessary proteolytic processing to generate the minimal CTL epitopes. Because MHC-I molecules on T cells are known to frequently recycle through endocytic compartment (59), where, in many cases, the free exchange of binding peptides takes place (60), it is conceivable that CTL epitopes originally bound to the APC's MHC could associate with the Th cells' recycling MHC-I molecules, while en route back to the cell surface. Preliminary results showing that chloroquine treatment of Th cells inhibits the formation of CTL epitopes from Th-CTL-linked peptides presented by pAPC provide support to this possibility (A. Undale, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…T cells activated with Con A or in an MLR spontaneously internalize their MHC-I molecules into endosome-like vesicles with a t 1/2 of ϳ1 h and recycle them from these vesicles to the cell surface with a t 1/2 of ϳ20 min (24,26,27). MHC-I containing a p H can be recycled to the cell surface still containing the p H (25).…”
Section: Discussionmentioning
confidence: 99%
“…Surface expression of MHC-I is also lost through internalization (20). Internalization of MHC-I occurs constitutively on activated lymphoid cells (23)(24)(25)(26)(27)). It appears that intact molecules are recycled to the cell surface and denatured molecules are shunted to a lysosomal pathway.…”
Section: Stability Ofmentioning
confidence: 99%
“…Endocytosis of MHC-I molecules has long been recognized, and occurs in a variety of different cell types (5)(6)(7)(8)(9). The process has biological implications for endosomal and lysosomal peptide loading and display, with the latter event designated as cross-presentation (14,33).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of spontaneous endocytosis of MHC-I molecules is higher in lymphoid T cells and monocytes than in B cells and can be induced by activation of protein kinase C-regulated pathways (5)(6)(7)(8)(9). Zuniga and colleagues (5) were the first to report that endocytosis of MHC-I molecules required the cytoplasmic domain and suggested that a conformational change was required for endocytosis.…”
mentioning
confidence: 99%